Physician ethics: undermined or enhanced by modes of payment? - Peter Zweifel; Katharina Janus (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Background: In the medical literature ((Begley (1987), Gervais et al. (1999), American Academy of Dermatology (2000)), the view prevails that any change away from fee-for-service (FFS) jeopardizes medical ethics, defined as motivational preference in this article. The objective of this contribution is to test this hypothesis by first developing two theoretical models of behavior, building on the pioneering works of Ellis and McGuire (1986) and Pauly and Redisch (1973). Medical ethics is reflected by a parameter α which indicates how much importance the physician attributes to patient well-being relative to his or her own income. Accordingly, a weakening of ethical orientation amounts to a fall in the value of α. While economic theory traditionally takes preferences as predetermined, such a change is possible in the light of Evolutionary Economics (Bolle, 2000). Methods: The model based on Ellis and McGuire (1986) depicts the behavior of a physician in private practice, while the one based on Pauly and Redisch (1973) applies to providers who share resources such as in hospital or group practice. Two changes in the mode of payment are analyzed, one from FFS to prospective payment (PP), the other, to pay-for-performance (P4P). One set of predictions relates physician effort to a change in the mode of payment; another, physician effort to a change in α, the parameter reflecting ethics. Using these two relationships, a change in ethics can observationally be related to a change in the mode of payment. The predictions derived from the models are pitted against several case studies from diverse countries. Results: A shift from FFS to PP is predicted to give rise to a negative observed relationship between medical ethics of physicians in private practice under a wide variety of circumstances, more so than a shift to P4P, which can even be seen as enhancing medical ethics provided physician effort has a sufficiently high marginal effectiveness in terms of patient well-being. This prediction is confirmed to a considerable degree by circumstantial evidence coming from the case studies. As to physicians working in hospital or group practice, the prediction is again that an observer will infer that a transition in hospital payment from FFS to PP weakens their ethical orientation. However, this prediction is not fully borne out; a likely reason is that hospitals also differ strongly in terms of their organizational culture, a factor that is not held constant in the case studies. A transition to P4P may lead observers to conclude that it actually enhances medical ethics of healthcare providers working in hospital or group practice. This prediction receives a degree of empirical support from the case studies. Conclusion: The claim that moving away from FFS undermines medical ethics is far too sweeping. It can only in part be justified by observed relationships, which even may suggest that a transition to P4P strengthens medical ethics.
Keywords: I11; J44; D64; 330